2013
DOI: 10.1002/ajpa.22339
|View full text |Cite
|
Sign up to set email alerts
|

A stable isotope (δ13C and δ15N) perspective on human diet on rapa nui (Easter Island) ca. AD 1400–1900

Abstract: Ecological and environmental evidence suggests that Rapa Nui was among the most marginally habitable islands in Eastern Polynesia, with only a fraction of the biotic diversity found on archipelagos to the west, and capable of sustaining many fewer cultigens traditionally transported by Polynesian colonizers. However, archaeological evidence for human dietary adaptations under such restrictions is limited. Little is known about the particulars of the subsistence base and dietary changes on Rapa Nui that may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 58 publications
6
46
2
Order By: Relevance
“…These values, along with similar faunal data, are comparable with bulk collagen results from other Rapa Nui studies (Commendador et al, 2013; Fogel et al, 1997; Polet & Bocherens, 2015). The δ 13 C and δ 15 N values of a prehistoric totora reed sample were −26.6‰ and 22.6‰, respectively, whereas the carbon and nitrogen isotopic values of a modern totora reed sample were −26.1‰ and 2.3‰, respectively.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…These values, along with similar faunal data, are comparable with bulk collagen results from other Rapa Nui studies (Commendador et al, 2013; Fogel et al, 1997; Polet & Bocherens, 2015). The δ 13 C and δ 15 N values of a prehistoric totora reed sample were −26.6‰ and 22.6‰, respectively, whereas the carbon and nitrogen isotopic values of a modern totora reed sample were −26.1‰ and 2.3‰, respectively.…”
Section: Resultssupporting
confidence: 90%
“…This is of particular relevance in isotopic studies as most invasive grasses on Rapa Nui are C 4 plants in the subfamilies Chloridoideae and Panicoidae, which make up ∼60% of the grass species, whereas indigenous grasses were dominantly C 3 plants (Finot et al, 2015). Secondly, Commendador et al (2013) showed that the Rapa Nui humans exhibited particularly high δ 15 N values, an observation also noted by Fogel et al (1997). Both studies suggested environmental factors, including the effect of seabird guano, as possible influences on this raised baseline.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations